1991
DOI: 10.1034/j.1600-0501.1991.020309.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal tissues and their counterparts around endosseous implants

Abstract: New technology coupled with a better understanding of tissue biology has played a key role in restoring the somewhat tarnished image of implant dentistry, Thanks to carefully conducted longitudinal studies, it has now become clear that the replacement of missing teeth by artificial implants integrated into the living tissues of the jaws is a predictable procedure, as long as certain guidelines are followed in the manufacture of the implant, its placement, its eventual functional loading, and its maintenance. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(57 citation statements)
references
References 0 publications
2
53
0
2
Order By: Relevance
“…44,45 Ossteointegrated implants show little mobility; hence, in contrast to the situation on abutment teeth, where a certain degree of misfit of a superstructure may be compensated by the resilience of the periodontium, misfit of FPDs seated on implant may cause a certain stress that is directly transmitted to the surrounding bone. 46 Before performing in vivo studies or applying materials for clinical use, in vitro tests should be undertaken to prove the materials' applicability and performance. In vitro tests can performed in a short period of time and have the advantages of reproducibility and the possibility of standardizing a test parameter.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Ossteointegrated implants show little mobility; hence, in contrast to the situation on abutment teeth, where a certain degree of misfit of a superstructure may be compensated by the resilience of the periodontium, misfit of FPDs seated on implant may cause a certain stress that is directly transmitted to the surrounding bone. 46 Before performing in vivo studies or applying materials for clinical use, in vitro tests should be undertaken to prove the materials' applicability and performance. In vitro tests can performed in a short period of time and have the advantages of reproducibility and the possibility of standardizing a test parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive multicenter studies have demonstrated the long-term success of implants, and many anatomical, histological, and cytological data are now available (Berglundh et al,199 1; Listgarten et al, 1991;Preti et al, 1996). From these studies, it has become apparent that the widespread success of clinical implantology is largely determined by the capability of bone to form rigid, load-bearing connections to implants and by the formation of a fibroblast-rich barrier tissue next to the titanium surface, which can protect the peri-implant bone against the oral environment.…”
Section: Introductionmentioning
confidence: 99%
“…As in the normal periodontium, the healthy mucosa has an essential role in protecting the peri-implant sulcus from bacterial invasion [19,20]. Regeneration of the attached mucosa around the implant post provides a protective barrier between the oral cavity and the internal environment.…”
Section: Introductionmentioning
confidence: 99%